A therapeutic community experience: the Fratello Sole community - Cagossi, Mario; Ciocca, Antonio; Pesola, Pier Ludovico (Medicina e Morale, 2024)
Therapeutic communities may be considered a specific response to the serious difficulties that any type of intervention encounters with regard to the problems posed by drug addiction. In fact, the complexity of these problems - social, psychological, educational - makes any intervention fail if it cannot refer to a broader project that supports it and gives it meaning.